PLT antigen discrepancy pattern among couples with recurrent abortion - Shad, Ghazal Ahmadzadeh; Ghasemi, Ali; Zadsar, Maryam; Shaeigan, Mojgan; Samiee, Shahram; Zare, Ahad (Frontiers in Medicine, 2024)
Background Recurrent abortion refers to a condition of two or more consecutive pregnancies without known etiology affected by miscarriage before the completion of the 20th week of gestational age. However, several hypotheses have been proposed, but not much data are available concerning the relationship between human platelet antigens (HPAs) polymorphisms and recurrent abortion. This study was conducted to evaluate the genetic differences between HPA-1, −2, −3, −5, and − 15 in Iranian couples with a history of recurrent abortion. Methods In this cross-sectional study, a total of 74 couples with at least 2 recurrent abortions without any known specified reasons enrolled in the study. HPA polymorphisms genotyping was performed by single-specific primer PCR. Genotype frequency was calculated using the Hardy–Weinberg equation. Results A total of 39 couples (52.7%) had HPA genotyping partial mismatches. The most common partial mismatch pairs were found concomitantly on both HPA-15a and HPA-15b in three couples (4%), followed by two (2.7%) on HPA-3a and one (1.3%) in each HPA-2b and HPA-5b. There was a deviation from the Hardy–Weinberg equilibrium in the HPA-2 and -5 systems. Conclusion The present study declared that partial mismatches of HPA-3 and -15 genotypes were common among Iranian couples due to the history of recurrent abortion and approximately half of the couples carried at least one HPA gene that was absent in their partners. Further studies might be helpful to clarify the association between HPA polymorphisms and recurrent abortion, such as an investigation into the alloantibodies against HPAs.